Pituitary abscess in an HIV-1-infected patient - Hiroyuki Yamazaki (SAGE Open Medical Case Reports, 2017)
Objectives: Pituitary abscess is a rare occurrence among pituitary conditions, but one which carries life-threatening potential. An immunocompromised status is a risk factor for the development of a pituitary abscess; however, literature describes only one case among HIV-infected patients. Methods and results: We present here a case of pituitary abscess in an HIV-1-positive patient, who demonstrated a shock status, disturbance of consciousness and generalized skin rash with laboratory findings of hypovolemia, acute inflammatory reaction and blood electrolyte abnormality. We first diagnosed the dermal manifestation as atypical generalized zoster, however, the other clinical findings could not be explained by VZV infection only. Combination with anamnesis, head magnetic resonance imaging scan and endocrine function test helped us to diagnose pituitary abscess. Although the etiology of the pituitary abscess could not be detected, the patient was successfully treated with antibiotics but followed by panhypopituitarism as sequela. Conclusion: A pituitary abscess should be considered in HIV-infected patients with endocrinological abnormalities, visual field defects, and central nervous system infection signs or symptoms, regardless of CD4 T-cell counts.